Comparison of molecular structure of alkali metal ortho substituted benzoates. Issue 3 (2010) - Świsłocka Świsłocka, R. R.
Abstract : The influence of the amino-, nitro-, methoxy-, hydroxy- and chloro-substituents in the ortho position towards the carboxylic group as well as alkali metal on molecular structure of benzoates was estimated. Optimized geometrical structures were calculated by B3LYP/6-311++G** method. Experimental FT-IR, FT-Raman and NMR spectra of the title compounds were recorded and analyzed. Data of chemical shifts in 1 H and 13 C NMR as well as wavenumbers and intensities in IR and Raman spectra of studied benzoate derivatives were analyzed in comparison with benzoic acid and with alkali metal benzoates.